A rare case of perosomus etumbis in a tellicherry goat - KUMAR, S SATHESH; VEL, K SENTHIL; Kannan, T P; GAJENDRAN, K (The Indian Journal of Animal Reproduction, 2023)
A double-headed monster fetus was delivered by caesarian section in a pluriparous crossbred (Desi x HF) pregnant cow was presented with acute labor and dystocia. Fetus was fully developed female calf with two heads joined by a single neck, two oral cavities, four eyes, two mandibles, two tongue, single esophagus, single thorax and abdomen, vulva, two fore limbs and two hind limbs which can be classified as Dicephalus Dipus Dibrachious Monster.